Behaviour of Nitrogen-Containing Molecule on the Si(001) Surface: Formation Process and Electronic Structure of the Pyrazine 1D Molecular Chain - Shimomura, Masaru (Asian Journal of Chemistry, 2013)
The formation process and electronic structure of a pyrazine 1D molecular chain formed on the Si(001)-(2×1) surface have been studied by density functional theory calculations and angle-resolved photoemission spectroscopy. It was found by the density functional theory cluster simulation with two pyrazine molecules adsorbed on the Si substrate that the most stable structure is obtained with linearly arranged inter-dimer-bridging pyrazine adsorbates. The angle-resolved photoemission spectroscopy measurements and the density functional theory calculations reveal that the pyrazine-saturated surface is semiconducting.